Conversion and Memory: A Dialogic Narrative Contextualisation of Liminal Identity - Kulavkova, Katica; Ilievska-Marjanovic, Jasmina (European Scientific Journal, ESJ, 2019)
Ethnic and religious conversion is deeply engraved in the history and memory of the Macedonian people, yet it remains a painful taboo subject. The paper is interested in the treatment of this topic in the New Macedonian Novel, which brought this problem from the collective unconscious into the public dialogue and shed light on its reoccurrence today. The analysis focuses on the novel The Book of Heavens (2000) by Krste Chachanski since it is equally representative of the topic of conversion to Islam in the Ottoman past, the poetics of the New Macedonian Novel, and the Macedonian dialogic and liminal identity. The Book of Heavens is set at the end of the 18th century in mountainous Macedonia, the forsaken Balkan periphery of the Ottoman Empire. It is centred around Adnan Pasha, the bi-religious and bi-cultural Janissary from Macedonia, his internal turmoil, and his quest for becoming the ethical warrior of his wilful choosing. The novel is a meta-historical and multi-voiced parable of dialogism and liminality in the context of human cognition, identity, and culture. But it is also a mythopoetic and magical realist saga for the ethical warrior, for the Macedonian tragically split and persecuted identity, for the syncretic civilisational borders and peripheries, and for protecting the palimpsest memory of human culture. The literaryhermeneutical analysis of conversion in this paper is inevitably a form of cultural and methodological syncretism. Self-plurality psychology and the linguistic, semiotic, and cultural philosophies of Bakhtin, Lotman, Ricoeur, and Eco are used in the analysis.